1980
DOI: 10.1111/j.2517-6161.1980.tb01094.x
|View full text |Cite
|
Sign up to set email alerts
|

Relative Curvature Measures of Nonlinearity

Abstract: Simple relative curvature measures of nonlinearity are developed to measure the extent of the nonlinearity in a model-experimental design-parameterization combination. We review the geometric aspects of linear and nonlinear least squares and, using the geometric concept of curvature, compute the maximum relative intrinsic curvature of the solution locus as well as the maximum relative parameter-effects curvature. The relative curvatures are independent of scale changes of the data and of the parameters so they… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
300
1
12

Year Published

1995
1995
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 413 publications
(314 citation statements)
references
References 13 publications
1
300
1
12
Order By: Relevance
“…It is obvious that for any flat estimation subspace ϕ = 0. Note that a similar measure of intrinsic nonlinearity is proposed before in Beale (1960) and it is actually expressed by the angle ϕ as sin 2 ϕ (Bates and Watts 1980).…”
Section: Indices Of Nonlinearitymentioning
confidence: 97%
See 2 more Smart Citations
“…It is obvious that for any flat estimation subspace ϕ = 0. Note that a similar measure of intrinsic nonlinearity is proposed before in Beale (1960) and it is actually expressed by the angle ϕ as sin 2 ϕ (Bates and Watts 1980).…”
Section: Indices Of Nonlinearitymentioning
confidence: 97%
“…According to the geometrical interpretation of linear LS-problem (3) (Fig. 1) the vector of the measured values specifies a point p O in the N -dimensional space of observations p whereas the K -dimensional subspace p C called estimation subspace (Bates and Watts 1980;Draper and Smith 1981) is an image Aq of the parametric space q in the observation space p. Obviously, since the vector δp O represents only measurement errors, the precise observationsp corresponding to the true parameter valuesq must belong to that subspace, in other words,p = p C (q) = Aq. Besides, it is important to note that in the linear case the estimation subspace is a flat, i.e.…”
Section: Ls-problem Its Geometry and Confidence Regionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although several measures of nonlinearity have been proposed [3,11,26], for this investigation, it is more useful to quantify the nonlinearity of a problem based on the effect of a linearity assumption on the magnitude of the likelihood function. We therefore define the nonlinearity measure for g at x 0 as the value of the function…”
Section: Single-parameter Test Problemmentioning
confidence: 99%
“…Box (1971) showed that the normalized bias is smaller than a specified function of the measure of non-linearity. Bates and Watts (1980) defined curvature measures for each direction in parameter space, and suggested to use the maximum over all directions. Hougaard (1985b) showed that the normalized bias and the skewness are smaller than specified functions of both Beales and Bates and Watts measures of non-linearity.…”
Section: Evaluation Of Non-normalitymentioning
confidence: 99%